2018
DOI: 10.1002/2017jb014684
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Extension of the Southern Mariana Margin

Abstract: Extension within the southern Mariana margin occurs both normal to and parallel to the trench. Trench‐normal extension takes place along focused and broad backarc spreading axes forming crust that is passively accreted to the rigid Philippine Sea plate flank to the northwest. To the southeast, trench‐parallel extension has split apart the Eocene‐Miocene forearc terrain accreting new crust diffusely over a 150–200 km wide zone forming a pervasive volcano‐tectonic fabric oriented at high angles to the trench and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 106 publications
(310 reference statements)
4
48
0
Order By: Relevance
“…Our study is consistent with the findings of Martínez et al () and Martinez et al (), who showed that lineaments display contrasting orientation on either side of the spreading axis at its southern end. From the spreading axis to the West Mariana Ridge, as described above, most lineaments are parallel to spreading axis orientations while from the spreading axis to the Mariana Ridge lineaments are normal to the spreading axis and the trench (oriented in ENE‐WSW and ESE‐WNW directions).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our study is consistent with the findings of Martínez et al () and Martinez et al (), who showed that lineaments display contrasting orientation on either side of the spreading axis at its southern end. From the spreading axis to the West Mariana Ridge, as described above, most lineaments are parallel to spreading axis orientations while from the spreading axis to the Mariana Ridge lineaments are normal to the spreading axis and the trench (oriented in ENE‐WSW and ESE‐WNW directions).…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, we infer that the trenchperpendicular tensional stress in the south arc-segment formed in a similar stress regime to structural lineaments of the Southern Mariana seafloor and was mainly caused by rollback of the subducting Pacific Plate. Martinez et al (2018) have suggested that the absence of discrete central arc volcanoes here is due to the more diffuse focus of deep arc stress. This contrasts with the concentration of stress in the deep arc lithosphere between 13.5°and 23°N, which produces a more distinct arc front.…”
Section: Southern Marianamentioning
confidence: 79%
See 2 more Smart Citations
“…The degree of arc evolution is variable along the IBM subduction system. The Southwest Mariana Rift (SWMR) is located at the southernmost Mariana, which separates the Western Mariana Ridge (WMR) and forearc blocks (Martinez et al, ). The SWMR differs from the Mariana Trough (MT) along the central‐north Mariana.…”
Section: Introductionmentioning
confidence: 99%